Jewish eschatology, early Christian christology, and the Testaments of the twelve patriarchs : collected essays of Marinus de Jonge. - Jonge, Marinus de, 1925- (Novum Testamentum, Supplements, 1991)
This volume, which appears on the occasion of Marinus de Jonge's retirement as Professor of New Testament at Leiden University, brings together twenty essays which he wrote recently for various periodicals and collective works. A number of articles deal with the expectation of the future in Jewish sources, like Ps. Sol., the Qumran Scrolls and Josephus. Closely connected with these are some essays on the question of how such titles as 'Christ', and 'Son of David' came to be applied to Jesus. Eleven essays delve into various important aspects of the Testaments of the Twelve Patriarchs: eschatology, ethics, paraenesis, but also their use of Jewish source material and their view of the history of God's dealing with man, a view related to that held by Justin and Hippolytus. This book throws light on the Jewish origins of early Christian theology and on its relationship with the Hellenistic culture in which it developed. The book also includes Marinus de Jonge's bibliography.